2021
DOI: 10.1155/2021/1678123
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Sports Action Recognition Based on GB‐BP Neural Network and Big Data Analysis

Abstract: In recent years, the application of the gradient boosting-back propagation (GB-BP) neural network algorithm in many industries has brought huge benefits, so how to combine the GB-BP neural network algorithm with sports has become a research hotspot. Based on this, this paper studies the application of the GB-BP neural network algorithm in wrestling, designs the sports athletes action recognition and classification model based on the GB-BP neural network algorithm, first analyzes the research status of wrestlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Wang's work commenced with a comprehensive analysis of the current state of wrestling action recognition, subsequently addressing and enhancing the limitations of existing action recognition and big data analysis techniques in the domain. Through these diverse endeavours, innovative solutions and algorithmic advancements are emerging to tackle complex problems across a spectrum of domains, driven by the growing availability and utilization of big data [15].…”
mentioning
confidence: 99%
“…Wang's work commenced with a comprehensive analysis of the current state of wrestling action recognition, subsequently addressing and enhancing the limitations of existing action recognition and big data analysis techniques in the domain. Through these diverse endeavours, innovative solutions and algorithmic advancements are emerging to tackle complex problems across a spectrum of domains, driven by the growing availability and utilization of big data [15].…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%